Staged treatment and acceptability guidelines in early psychosis study (STAGES): A randomized placebo controlled trial of intensive psychosocial treatment plus or minus antipsychotic medication for first‐episode psychosis with low‐risk of self‐harm or aggression. Study protocol and baseline characteristics of participants. Issue 4 (19th July 2018) - O'Donoghue, Brian; Francey, Shona M.; Nelson, Barnaby; Ratheesh, Aswin; Allott, Kelly; Graham, Jessica; Baldwin, Lara; Alvarez‐Jimenez, Mario; Thompson, Andrew; Fornito, Alex; Polari, Andrea; Berk, Michael; et al.
Abstract : Aim: It is now necessary to investigate whether recovery in psychosis is possible without the use of antipsychotic medication. This study will determine (1) whether a first‐episode psychosis (FEP) group receiving intensive psychosocial interventions alone can achieve symptomatic remission and functional recovery; (2) whether prolonging the duration of untreated psychosis (DUP) in a sub‐group according to randomisation will be associated with a poorer outcome and thereby establish whether the relationship between DUP and outcome is causative; and (3) whether neurobiological changes observed in FEP are associated with the psychotic disorder or antipsychotic medication. Baseline characteristics of participants will be presented. Methods: This study is a triple‐blind randomized placebo‐controlled non‐inferiority trial. The primary outcome is the level of functioning measured by the Social and Occupational Functioning Assessment Scale at 6 months. This study is being conducted at the Early Psychosis Prevention and Intervention Centre, Melbourne and includes young people aged 15 to 24 years with a DSM‐IV psychotic disorder, a DUP less than 6 months and not high risk for suicide or harm to others. Strict discontinuation criteria are being applied. Participants are also undergoing three 3‐Tesla‐MRI scans. Results: Ninety participants have been recruited and baseline characteristics are presented. Conclusions: Staged treatment and acceptability guidelines in early psychosis will determine whether antipsychotic medications are indicated in all young people with a FEP and whether antipsychotic medication can be safely delayed. Furthermore, the relative contribution of psychotic illness and antipsychotic medication in terms of structural brain changes will also be elucidated. The findings will inform clinical practice guidelines.